Survey of Malaria Vectors in the Rainy Season in Inalipue Village, Wajo District, South Sulawesi - Naswir, Naswir; Hamzah, Erlina; Syukur, Muhammad; Saleh, Muhammad (Program Studi Kesehatan Masyarakat UIN Alauddin Makassar, 2024)
Climate change will affect the physical and biological environment that supports the development of various infectious diseases, including malaria. Wajo District, particularly Inalipue Village in Tanasitolo Sub-district, faces a major challenge in controlling the malaria vector, the Anopheles mosquito. The main objective of this survey was to identify and understand the environmental factors that contribute to Anopheles mosquito population density in Inalipue Village. Data were obtained by capturing adult mosquitoes using the Human Landing Collection (HLC) method as well as surveying Anopheles mosquito larval breeding sites. Mosquito trapping was conducted inside and outside the house and around livestock pens. Anopheles barbirostris was the most dominant species, found in all capture methods with the highest Man Biting Rate (MBR) of 1.00 for outdoor capture. Anopheles nigerrimus and Anopheles vagus were also found, although in smaller numbers. Of the 17 breeding habitat sites, 5 showed positive larval results. Water temperature, pH, and the presence of flora and fauna in these habitats varied, but most had ideal conditions for mosquito breeding. Anopheles barbirostris shows high adaptation to a wide range of habitats, making it the main vector. These findings provide a strong basis for local governments and health agencies to plan and implement more effective and integrated malaria control programs.